Alpha4 integrin binding interfaces on VCAM-1 and MAdCAM-1. Integrin binding footprints identify accessory binding sites that play a role in integrin specificity. - Newham, P; Craig, SE; Seddon, G; Schofield, N; Rees, A; Edwards, R; Jones, E; Humphries, M (1997)
Integrins are a family of heterodimeric adhesion receptors that mediate cellular interactions with a range of matrix components and cell surface proteins. Vascular cell adhesion molecule-1 (VCAM-1) is an endothelial cell ligand for two leukocyte integrins (alpha4beta1 and alpha4beta7). A related CAM, mucosal addressin cell adhesion molecule-1 (MAdCAM-1) is recognized by alpha4beta7 but is a poor ligand for alpha4beta1. Previous studies have revealed that all alpha4 integrin-ligand interactions are dependent on a key acidic ligand motif centered on the CAM domain 1 C-D loop region. By generating VCAM-1/MAdCAM-1 chimeras and testing recombinant proteins in cell adhesion assays we have found that alpha4beta1 binds to the MAdCAM-1 adhesion motif when present in VCAM-1, but not when the VCAM-1 motif was present in MAdCAM-1, suggesting that this region does not contain all of the information necessary to determine integrin binding specificity. To characterize integrin-CAM specificity further we measured alpha4beta1 and alpha4beta7 binding to a comprehensive set of mutant VCAM-1 constructs containing amino acid substitutions within the predicted integrin adhesion face. These data revealed the presence of key "regulatory residues" adjacent to integrin contact sites and an important difference in the "footprint" of alpha4beta1 and alpha4beta7 that was associated with an accessory binding site located in VCAM-1 Ig domain 2. The analogous region in MAdCAM-1 is markedly different in size and sequence and when mutated abolishes integrin binding activity.